Complications of immediate breast reconstruction after total mastectomy using conical and non-conical prostheses - Rogério de Oliveira Ribeiro; Salustiano Gomes de Pinho Pessoa (Revista Brasileira de Cirurgia Plástica)
Introduction: In the biennium 2016-2017, approximately 2,160 new cancer cases were identified by the Brazilian National Cancer Institute (Instituto Nacional do Câncer; INCA) for the state of Ceará and 57,960 new cases for every 100,000 women in Brazil. Breast reconstruction with alloplastic implants presents early and late surgical complications directly or indirectly related to the surgical technique used to perform mastectomy and implantation of the synthetic material. This study aimed to analyze the complications found in a group of patients submitted for immediate breast reconstruction using conical and non-conical prostheses. Methods: This is a cross-sectional, retrospective, observational cohort study that analyzed the medical records of patients who underwent skin-sparing total mastectomy with immediate breast reconstruction using conical and non-conical prostheses, performed by the Plastic Surgery and Reconstructive Microsurgery Service at the HUWC of the Federal University of Ceará from January 2016 to 2018. Results: A total of 13 (54.1%) patients presented with complications. The conical prostheses showed the highest number of complications, i.e., 7 (63.6%) patients, whereas only 6 (46.1%) patients with non-conical prostheses had complications. Conclusion: Our study showed a higher frequency of complications with the use of conical prostheses when compared to non-conical prostheses, mainly due to the formation of a sore area at the tip of the conical prosthesis that resulted in extrusion.